Risk analysis and countermeasures of TBM tunnelling over the operational tunnel - Lu, Feng; Li, Linlong; Chen, Zhenyu; Liu, Maoyi; Li, Pinpin; Gao, Xinqiang; Ji, Changjun; Gong, Lun (Frontiers in Earth Science, 2023)
To study the risk and control countermeasures of the TBM tunnel construction adjacent to the operational railway tunnel, based on the TBM tunnel project of Chongqing Rail Transit Line 5, this paper first evaluates the quality health degree of the operational tunnel lining (OTL) structure according to the on-site structural inspection. Then, the displacement, internal force, and proximity influence scope influenced by the metro TBM tunnel construction are studied using numerical simulation. Finally, the corresponding control countermeasures are proposed. The results show that: (1) The adjacent construction of the upper TBM tunnel will lead to the uplift deformation trend of the lower operational tunnel, and the uplift deformation of the vault is greater than that of the ballast bed. The influence scope is roughly a parallelogram, with the long axis parallel to the operational tunnel and the short axis parallel to the new TBM subway tunnel. (2) TBM tunnelling over the operational tunnel will cause the transformation of the mechanical mode of the OTL structure from the small eccentric compression mode to the large eccentric compression mode. The OTL structure between the left and right lines of TBM is unfavorable. (3) The longitudinal curve of the bending moment and axial force of the OTL fluctuates greatly within the influence range. The bending moment and axial force are reduced in operational tunnel construction joints. Based on field evaluation and numerical analysis, this paper puts forward some risk control countermeasures, such as TBM tunnelling parameters control, pea-gravel backfilling, backfill grouting, and bottom grouting, which can effectively solve the risk of the operational tunnel structure in the adjacent construction. This study has important reference value for risk control and safety assessment of tunnel in complex adjacent tunnel construction.